Efficacy and safety of a magnesium stearate paclitaxel coated balloon catheter in the porcine coronary model. (15th May 2021) - Bettink, Stephanie; Löchel, Melanie; Peters, Daniel; Haider, Wolfram; Speck, Ulrich; Scheller, Bruno
Abstract: Background: Local administration of growth-inhibiting substances such as paclitaxel or sirolimus could reduce the risk of restenosis. In the drug coated balloon (DCB) technology the coating and the applied dose seem to play a major role. The aim of the present preclinical studies was to investigate the efficacy and safety of a specific DCB with paclitaxel as active ingredient and magnesium stearate as excipient. Methods: Evaluation of the coating, drug release and transfer was done ex vivo and in vivo on peripheral arteries. A porcine coronary stent model was chosen to provoke intimal thickening. Conventional uncoated balloons were compared with paclitaxel urea and paclitaxel magnesium stearate coated balloons. QCA and histomorphometry was performed on treated vessels. Three areas of the heart were histologically examined for pathological changes. Results: QCA and histomorphometry revealed no differences in baseline data between treatment groups. All DCB groups showed a significant reduction of angiographic and histologic parameters describing neointimal formation 4 weeks after treatment (e.g. mean angiographic late lumen loss all coated 0.31 ± 0.18 mm versus 0.91 ± 0.37 mm in the uncoated balloon group). There were no device-related animal deaths or clinical abnormalities. In spite of very slight-to-slight microscopic findings limited to small arterial vessels in downstream tissue there was no change in left ventricular ejection fraction or angiographic presentation of small side branches of treated arteries. Conclusion: Paclitaxel DCB using stearate as excipient show a high efficacy in reducing neointima formation after experimental coronary intervention. No evidence of myocardial damage resulting from distal embolization was found. Highlights: Paclitaxel/MgS coated balloons showed low drug split off and drug transfer comparable to paclitaxel/urea coated balloons. All tested DCBs achieved reduced neointima formation (diameter stenosis, p  = 0.001) and less luminal narrowing (late lumen loss, p  = 0.001). No microembolization despite of microembolization was detected in side branches of the treated vessels nor in myocardial tissue.